The Relevance of Energy Consumption and Economic Growth Indicators to Anthropogenic Disasters - Sofyan Maftuahnan (Efficient: Indonesian Journal of Development Economics, 2025)
This study aims to analyze the effects of GDP per capita, Foreign Direct Investment (FDI), primary energy consumption per capita, and electricity consumption per capita on carbon emissions in Indonesia, both in the short and long term, during the period from 1974 to 2022. The data for this study were obtained from the World Bank, Enerdata, the Ministry of Energy and Mineral Resources, and Our World in Data. The Error Correction Model (ECM) was employed to address empirical questions regarding the long-term and short-term relationships among the research variables. The findings indicate that GDP per capita has a positive but not significant impact on carbon emissions in both the short and long term. Moreover, FDI shows a positive and significant relationship with carbon emissions in the long term but does not exhibit a significant relationship in the short term. These results also highlight the negative impact of FDI, proving the occurrence of the pollution haven hypothesis in Indonesia. On the other hand, both primary energy consumption per capita and electricity consumption per capita show a positive and significant correlation with carbon emissions in both the short and long term.